MHD free convection boundary layer flow on a horizontal circular cylinder in a williamson hybrid ferrofluid under heat generation/absorption - Marjan, Mohd Daud; Norhafizah, Md Sarif; Ong, Huei Ruey; Muhammad Khairul Anuar, Mohamed (Universiti Teknologi Malaysia, 2025)
This study investigates the free convection boundary layer flow past a horizontal circular cylinder immersed in Williamson hybrid ferrofluid. Magnetite (Fe3O4) and gold (Au) nanoparticles are suspended in blood which serves as the non-Newtonian Williamson based fluid. The effects of heat generation/absorption and magnetohydrodynamic (MHD) were incorporated into the mathematical formulation. The governing non linear partial differential equations describing the flow and heat transfer phenomena are non-dimensionalized and reduced to a system of ordinary differential equations. These equations were solved numerically using the Keller-box implicit finite difference method. The Keller-box algorithm is implemented in MATLAB software to compute the graphical representations, and the influence of pertinent parameters on skin friction coefficient, Nusselt number, velocity and temperature profiles. The results show that the hybrid ferrofluid significantly exhibits superior convective heat transfer and skin friction performance compared to conventional ferrofluids containing only a single type of nanoparticle. Moreover, the presence of heat generation/absorption was found to strongly influence the thermal boundary layer thickness, providing new insights into the optimization of hybrid ferrofluids for engineering and biomedical applications.